qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
$$x ^ { 2 } - x - 12 = 0$$
$\begin{array} {l} x = 4 \\ x = - 3 \end{array}$
Calculate using the quadratic formula
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 1 \right ) \pm \sqrt{ \left ( - 1 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 12 \right ) } } { 2 \times 1 }$
$ $ Simplify Minus $ $
$x = \dfrac { 1 \pm \sqrt{ \left ( - 1 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 12 \right ) } } { 2 \times 1 }$
$x = \dfrac { 1 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 12 \right ) } } { 2 \times 1 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 1 \pm \sqrt{ 1 ^ { 2 } - 4 \times 1 \times \left ( - 12 \right ) } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 \pm \sqrt{ 1 ^ { 2 } - 4 \times 1 \times \left ( - 12 \right ) } } { 2 \times 1 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 \pm \sqrt{ 49 } } { 2 \times 1 } }$
$x = \dfrac { 1 \pm \sqrt{ \color{#FF6800}{ 49 } } } { 2 \times 1 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { 1 \pm \color{#FF6800}{ 7 } } { 2 \times 1 }$
$x = \dfrac { 1 \pm 7 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { 1 \pm 7 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 \pm 7 } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 + 7 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 1 - 7 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 7 } } { 2 } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$ $ Add $ 1 $ and $ 7$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 8 } } { 2 } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 8 } { 2 } } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 4 } { 1 } } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 4 } { 1 } } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$ $ Reduce the fraction to the lowest term $ $
$\begin{array} {l} x = \color{#FF6800}{ 4 } \\ x = \dfrac { 1 - 7 } { 2 } \end{array}$
$\begin{array} {l} x = 4 \\ x = \dfrac { \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 7 } } { 2 } \end{array}$
$ $ Subtract $ 7 $ from $ 1$
$\begin{array} {l} x = 4 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 6 } } { 2 } \end{array}$
$\begin{array} {l} x = 4 \\ x = \color{#FF6800}{ \dfrac { - 6 } { 2 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = 4 \\ x = \color{#FF6800}{ \dfrac { - 3 } { 1 } } \end{array}$
$\begin{array} {l} x = 4 \\ x = \dfrac { - 3 } { \color{#FF6800}{ 1 } } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = 4 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo